The Effect of Principal’s Academic Supervision and the Role of School’s Committees on Teacher’s Performance - Wijayanti, Rut Erna; Widayatsih, Tri; Wahidy, Achmad (Yayasan Sembilan Pemuda Indonesia, 2023)
In 188 countries, school closures caused by the Covid-19 pandemic have prevented more than 91% of students from attending classes (UN, 2020). In the new normal period where face-to-face learning starts to be carried out again as it is today, teachers who perform well will become the driving force for expediting the teaching and learning process. The performance of State Vocational School instructors in Ogan Ilir District will be examined in this quantitative study in relation to the influence of the school principal’s academic oversight and the function of the school committee. Using a Likert scale, a questionnaire was employed as the data gathering tool. The Slovin approach was used to choose 158 participants from a population of 261 State Vocational High School instructors in the Ogan Ilir Regency. The range of norms for each variable falls into the sufficient category, according to the results of the descriptive statistical analysis. Inferential statistics that employ both basic and multiple linear regression to evaluate hypotheses. The analysis’s findings indicate that the school principal’s oversight of academics and the function of the school committee have a favorable impact on the performance of instructors at State Vocational Schools in the Ogan Ilir District.